Global Phylogeny of Mycobacterium avium and Identification of Mutation Hotspots During Niche Adaptation - Mizzi, Rachel; Plain, Karren M.; Whittington, Richard; Timms, Verlaine J. (Frontiers in Microbiology, 2022)
Mycobacterium avium is separated into four subspecies: M. avium subspecies avium (MAA), M. avium subspecies silvaticum (MAS), M. avium subspecies hominissuis (MAH) and M. avium subspecies paratuberculosis (MAP). Understanding the mechanisms of host and tissue adaptation leading to their clinical significance is vital to reduce the economic, welfare and public health concerns associated with diseases they may cause in humans and animals. Despite substantial phenotypic diversity, the subspecies nomenclature is controversial due to high genetic similarity. Consequently, a set of 1230 M. avium genomes was used to generate a phylogeny, investigate SNP hotspots and identify subspecies-specific genes. Phylogeny reiterated the findings from Turenne, C. Y. et al. (2008 and establish that Mycobacterium avium is a species made up of one highly diverse subspecies, known as MAH, and at least two clonal pathogens, named MAA and MAP. Pan-genomes identified coding sequences unique to each subspecies and in conjunction with a mapping approach, mutation hotspot regions were revealed compared to the reference genomes for MAA, MAH and MAP. These subspecies-specific genes may serve as valuable biomarkers, providing a deeper understanding of genetic differences between M. avium subspecies and the virulence mechanisms of mycobacteria. Furthermore, SNP analysis demonstrated common regions between subspecies that have undergone extensive mutations during niche adaptation. The findings provide insights into host and tissue specificity of this genetically conserved but phenotypically diverse species, with the potential to provide new diagnostic targets and epidemiological and therapeutic advances.